Identifcation and Location of Partial Discharge Defects in Medium Voltage AC Cables - Shafiq, Muhammad; Robles, Guillermo; Hussain, Amjad; Kauhaniemi, Kimmo; Lehtonen, Matti (Nordic Insulation Symposium, 2019)
The presence of partial discharge (PD) in electrical equipment is the confirmation or indication of an ongoing degradation of its dielectric insulation. PD study is a widely used tool for condition monitoring of medium voltage (MV) cables. The location of the defects can be considered as one of the most important tasks of diagnosis in underground installations of MV cables. A lot of references can be found on the location of single PD sources along the cable. However, several PD defects can be active simultaneously along a cable section. This paper presents an experimental study on a MV cable having two PD sources and noise. Adopting one end measurement technique, a high frequency current transformer (HFCT) is used to capture the PD current pulses. A simple approach of identification of the PD signals originated from different PD sources is presented based on wave-shape study along with a time domain reflectometry analysis. The presented measurement methodology and time domain analysis technique provides a convenient way for detection and location of more than one PD sources along a cable section.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|